Müllerianosis of the urinary bladder may simulate a bladder cancer: a case report - Bocchialini, Tommaso; Ziglioli, Francesco; Palmieri, Gerardo; Barbieri, Antonio; Infranco, Antonia; Milandri, Riccardo; Simonetti, Elisa; Ferretti, Stefania; Maestroni, Umberto (Acta Biomedica Atenei Parmensis, 2021)
Müllerianosis is an extremely rare entity consisting of an admixture of 2 or more müllerian tissues. We report the case of a 61 years old woman who came to our attention with hypogastric pain and dysuria. She was in menopause and had a previous history of cesarean section. Ultrasound and CT-scan of the abdomen showed a proliferative bladder lesion close to the left ureteric orifice. Transurethral resection of the bladder (TUR-B) was performed. Histopathological examination of the specimens was negative for bladder cancer and revealed the presence of endosalpingeal tissue. Postoperative course was unremarkable as well as follow up at 12 months. A proper knowledge and awareness of this disease, even if rare, is necessary for an accurate differential diagnosis and to perform an appropriate treatment.